2010
DOI: 10.1002/ajim.20895
|View full text |Cite
|
Sign up to set email alerts
|

Occupations and industries in France at high risk for pleural mesothelioma: A population‐based case–control study (1998–2002)

Abstract: This report provides new insight into the epidemiology of mesothelioma, confirming risks for occupational activities reported earlier and pointing out risks in activities never previously reported. It offers guidance to authorities for the compensation of asbestos victims and for prevention in at-risk activities still involving asbestos-containing products.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
37
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 31 publications
5
37
0
Order By: Relevance
“…These data are consistent with the meta-analysis of epidemiologic studies that investigated the incidence of lung cancer and pleural mesothelioma in automobile mechanics and failed to demonstrate increased metarelative risks (Wong, 2001;Goodman et al, 2004). Our data are also consistent with the results of a recently published population-based case-control study (Rolland et al, 2010) that reported a slight but not significant increased risk of pleural mesothelioma in male car mechanics (odds ratio 5 1.50; 95% confidence interval: 0.76-2.95).…”
Section: Discussionsupporting
confidence: 82%
“…These data are consistent with the meta-analysis of epidemiologic studies that investigated the incidence of lung cancer and pleural mesothelioma in automobile mechanics and failed to demonstrate increased metarelative risks (Wong, 2001;Goodman et al, 2004). Our data are also consistent with the results of a recently published population-based case-control study (Rolland et al, 2010) that reported a slight but not significant increased risk of pleural mesothelioma in male car mechanics (odds ratio 5 1.50; 95% confidence interval: 0.76-2.95).…”
Section: Discussionsupporting
confidence: 82%
“…The study design was previously reported in detail 18. Cases were identified through the PNSM from 1998 to 2002 and certified by a standardised diagnostic confirmation procedure 17.…”
Section: Methodsmentioning
confidence: 99%
“…The patient was asymptomatic and the physical examination was unremarkable. A chest CT scan was performed, according to the French Recommendations for Workers with Known Asbestos Exposure; this demonstrated pleural thickenings [11]. …”
Section: Case Reportsmentioning
confidence: 99%